Implementation of Merdeka Curriculum for Sundanese Language Subject Towards the Era of Smart Society 5.0 - Nurjanah, Nunuy; Sudaryat, Yayat; Haerudin, Dingding; Srihilmawati, Rostika; Darajat, Danan (PT Mattawang Mediatama Solution, 2024)
The existence of regional languages currently continues to decrease the number of speakers. Transformation into digital form as an alignment of the smart society 5.0 era is considered a preventive measure to prevent this condition from worsening. This paper aims to explain how the Merdeka Curriculum for Sundanese Language Subjects Towards the Era of Smart Society 5.0. Smart Society 5.0 was initiated to solve various kinds of issues in all fields of human life. To realize a revolution, it is necessary to have a lot of capital as a foundation, in this case improving the quality of human resources owned by Indonesia is crucial. There are 5 important domains in developing the quality of human resources: professionalism, ability to compete, functional competence, participatory excellence, and cooperation.